The Impact of Divorce on Child Custody (Decision Study Number 150/Pdt.G/2021/PA.Btl) - Rahman, Abi Syauqi; Heriyani, Endang (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
The Compilation of Islamic Law regulates the effects of divorce on children in Article 105 letter (a), which reads: